Tomistyczne źródła poetyckiej estetyki Czesława Miłosza - Bałdyga, Katarzyna (Colloquia Litteraria, 2020)
Thomist Sources of Czesław Miłosz’s Poetic Aesthetics The article shows the essays and poetry of Czeslaw Milosz in the context of Aquinas expressions about beauty. The fondness of the concrete, visibility, the realistic world and giving justice to these parts in the poetry and art had to lead to rejection of the poetry of a pure form and abstraction. Milosz – as a hunter grasping the reality – protects the word which is connected with reality. He put the existence in the centre of his poetical world. The realistic and objective existence was a basic experience for him. This experience was noted down in his work. Thus, the inspiration by saint Thomas Aquinas affected his artistic choices. In the work of the poet, it is visible that the texts of Aquinas had been his set books for many years. This tasting of the philosopher’s work can be best seen in the comparison of the writing practice of Miłosz with the particular matters coming from Summa Theologiae or Art and Wisdom of Maritain (the contemporary Thomist read by Miłosz).